Processing maps based on polymerization modelling of thick methacrylic laminates. (November 2020) - Gayot, Sarah F.; Bailly, Christian; Pardoen, Thomas; Gérard, Pierre; Van Loock, Frederik
Abstract: Control of the in-situ polymerization of thick methacrylic laminates is essential to minimize cavitation due to monomer boiling. To this end, a computationally efficient thermochemical model is developed to predict the temperature and degree of monomer conversion during polymerization of a methyl methacrylate (MMA)-based resin in a fibrous preform. The model couples the self-accelerating exothermic free-radical bulk polymerization of MMA (gel effect) with the heat transfer within the preform and to the environment. The predicted temperature profiles are in excellent agreement with experimental data measured during a series of in-situ polymerization tests with different heating conditions and preform thicknesses. Processing diagrams are constructed to reveal the regimes of interest for the production of thick fiber-reinforced methacrylic composites without voids induced by monomer boiling. Graphical abstract: Unlabelled Image Highlights: Thick composite laminates are produced via vacuum infusion and in-situ polymerization of a methyl methacrylate-based resin. Monomer boiling due to the self-accelerating polymerization reaction can lead to macro-sized voids in the laminate. A thermochemical model is developed to predict the maximum temperature within the laminate during in-situ polymerization. The predicted temperature profiles are in excellent agreement with those measured for different processing conditions. Processing maps reveal optimal heating conditions leading to short cycle times without thermally-induced cavitation.